Vegetation restoration improved aggregation stability and aggregated-associated carbon preservation in the karst areas of Guizhou Province, southwest China - Hui Yang; Hui Long; Xuemei Li; Xiulong Luo; Yuanhang Liao; Changmin Wang; Hua Cai; Yingge Shu (PeerJ, 2024)
Background The change in the soil carbon bank is closely related to the carbon dioxide in the atmosphere, and the vegetation litter input can change the soil organic carbon content. However, due to various factors, such as soil type, climate, and plant species, the effects of vegetation restoration on the soil vary. Currently, research on aggregate-associated carbon has focused on single vegetation and soil surface layers, and the changes in soil aggregate stability and carbon sequestration under different vegetation restoration modes and in deeper soil layers remain unclear. Therefore, this study aimed to explore the differences and relationships between stability and the carbon preservation capacity (CPC) under different vegetation restoration modes and to clarify the main influencing factors of aggregate carbon preservation. Methods Grassland (GL), shrubland (SL), woodland (WL), and garden plots (GP) were sampled, and they were compared with farmland (FL) as the control. Soil samples of 0–40 cm were collected. The soil aggregate distribution, aggregate-associated organic carbon concentration, CPC, and stability indicators, including the mean weight diameter (MWD), fractal dimension (D), soil erodibility (K), and geometric mean diameter (GMD), were measured. Results The results showed that at 0–40 cm, vegetation restoration significantly increased the >2 mm aggregate proportions, aggregate stability, soil organic carbon (SOC) content, CPC, and soil erosion resistance. The >2 mm fractions of the GL and SL were at a significantly greater proportion at 0–40 cm than that of the other vegetation types but the CPC was only significantly different between 0 and 10 cm when compared with the other vegetation types (P < 0.05). The >2 mm aggregates showed a significant positive correlation with the CPC, MWD, and GMD (P < 0.01), and there was a significant negative correlation with the D and K (P < 0.05). The SOC and CPC of all the vegetation types were mainly distributed in the 0.25–2 mm and <0.25 mm aggregate fractions. The MWD, GMD, SOC, and CPC all gradually decreased with increasing soil depth. Overall, the effects of vegetation recovery on soil carbon sequestration and soil stability were related to vegetation type, aggregate particle size, and soil depth, and the GL and SL restoration patterns may be more suitable in this study area. Therefore, to improve the soil quality and the sequestration of organic carbon and reduce soil erosion, the protection of vegetation should be strengthened and the policy of returning farmland to forest should be prioritized.